Pengalaman Mahasiswa dalam Memanfaatkan ChatGPT untuk Mendukung Aktivitas Akademik: Studi Fenomenologi di Universitas 17 Agustus 1945 Surabaya - Abigaiel C. Lesbasa; Iftahul Jannah; Azizah Ainun Mari'a; Muhammad Rahmtullah Kautsari; Tan Evan Tandiyono (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
The rapid development of Artificial Intelligence (AI) has transformed various aspects of higher education, particularly through the increasing use of ChatGPT as an academic support tool. This study aims to explore and understand students’ experiences in utilizing ChatGPT to support their academic activities at Universitas 17 Agustus 1945 Surabaya. A qualitative approach with a phenomenological design was employed to capture the lived experiences of students who actively use ChatGPT in their learning process. Data were collected through in-depth interviews with four students from different study programs and analyzed using thematic analysis. The findings reveal four major themes. First, ChatGPT is widely used to support learning activities, including understanding course materials, generating ideas, organizing assignments, and solving technical problems. Second, students perceive ChatGPT as a practical and efficient learning aid that facilitates access to information and improves academic productivity. Third, although students acknowledge the benefits of ChatGPT, they also recognize the risk of technological dependence and the potential decline in critical thinking skills when the technology is used excessively. Fourth, students demonstrate awareness of the limitations of AI-generated information by conducting verification through journals, books, and other credible sources before using the information for academic purposes. The study concludes that ChatGPT has become an integral part of students’ academic experiences by providing efficiency and learning support. However, its use requires critical awareness and responsible academic practices to ensure that technological assistance enhances, rather than replaces, independent learning and critical thinking.